Chemogenetic inhibition of corticotropin releasing hormone neurons in the paraventricular nucleus attenuates traumatic stress-induced deficit of NREM sleep, but not REM sleep in mice - Andrey Kostin; Natalia Suntsova; Sunil Kumar; Irma Gvilia (Stress)
Present study was aimed to elucidate the role of corticotropin releasing hormone (CRH) neurons located in the paraventricular nucleus of the hypothalamus (PVN) in the mechanisms of stress-induced insomnia. Experiments were done in the rodent model of traumatic stress, mice exposure to the predator (rat) odor. Sleep changes associated with this model of stress were first assessed in adult male C57BL/6J wild-type mice (n = 12). The effect of chemogenetic silencing of CRH neurons within the PVN on traumatic stress-induced insomnia was examined in adult male CRH-ires-Cre mice using designer receptors exclusively activated by designer drugs (DREADD) technology. Animals received bilateral injections of inhibitory DREADD vector AAV-hSyn-DIO-hM4Di-mCherry (n = 10) or control AAV-hSyn-DIO-mCherry virus (n = 10) into the PVN during surgery. The DREADD was activated by intraperitoneal injection of clozapine-N-oxide (CNO) prior to the induction of traumatic stress. The exposure of mice to rat odor induced strong long-lasting suppression of both non-rapid eye movement (NREM) and rapid eye movement (REM) sleep stages in both experiments. Selective suppression of CRH neurons within the PVN alleviated acute insomnia by significantly increasing the time spent in NREM sleep but it did not counteract the stress-induced deficit in REM sleep. These findings suggest a specific role for CRH-secreting neurons within the PVN in the suppression of NREM sleep during acute insomnia caused by predator odor stress, whereas REM sleep suppression is controlled by a different mechanism.